The characteristics of jump ability in elite adolescent athletes and healthy males: The development of countermovement and rebound jump ability - Tauchi, K.; Endo, T.; Ogata, M.; Matsuo, A.; Iso, S. (International Journal of Sport & Health Science, 2008)
The purpose of this study was to clarify the characteristics of jump ability in elite adolescent male athletes for the purpose of comparing them to healthy coeval males by referring to the results reported by Endo, et al., (2007). One hundred and twenty elite male athletes (alpine skiers, fencers, soccer players, track and field sprinters and jumpers, and weight lifters) aged 18 to 24 yrs and 316 healthy males aged 19 and 20 yrs performed countermovement jumps (CMJ) and five- repeated rebound jumps (5RJ) on a mat switch system. CMJ and 5RJ abilities were evaluated by jump height and RJ-index (=jump height/ground contact time), respectively. Although the jump height in CMJ and the RJ-index in 5RJ developed from ages 6 to 18 yrs, these values reached a plateau between the ages of 18 and 20 yrs in healthy males, elite athletes further developed after age 18. When the values for the healthy males in the present study were added to the results obtained for 1137 boys by Endo, et al., (2007), the regression line and correlation coefficient between jump height in CMJ and the RJ-index in 5RJ changed only slightly. However, the values for elite adolescent athletes tended to appear in the upper right from the population ages of 6 to 20 yrs; moreover, the scattering exhibited wide variation. The results revealed that although jump ability in healthy adolescent males changed little after age 18, jump ability in elite coeval athletes were superior after age 18 and that individual differences increased according to the length of specific training in each sport.